2019
DOI: 10.1073/pnas.1813230116
|View full text |Cite
|
Sign up to set email alerts
|

Competitive binding predicts nonlinear responses of olfactory receptors to complex mixtures

Abstract: In color vision, the quantitative rules for mixing lights to make a target color are well understood. By contrast, the rules for mixing odorants to make a target odor remain elusive. A solution to this problem in vision relied on characterizing receptor responses to different wavelengths of light and subsequently relating these responses to perception. In olfaction, experimentally measuring receptor responses to a representative set of complex mixtures is intractable due to the vast number of possibilities. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…Both properties would enhance the accuracy and speed of detectability of mixtures over pure odorants. Competitive binding in mixtures can also predict more complex properties of sensory receptor responses, such as synergy, antagonism and overshadowing (Reddy, Zak, Vergassola, & Murthy, 2018;Singh, Murphy, Balasubramanian, & Mainland, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both properties would enhance the accuracy and speed of detectability of mixtures over pure odorants. Competitive binding in mixtures can also predict more complex properties of sensory receptor responses, such as synergy, antagonism and overshadowing (Reddy, Zak, Vergassola, & Murthy, 2018;Singh, Murphy, Balasubramanian, & Mainland, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical work has shown that a variety of non-linear interactions among multiple ligands at the same receptor can readily arise with a simple two-step model of receptor activation (Reddy et al, 2018). Experimental work in vitro in OSNs has suggested the existence of non-linear interactions, especially antagonism (Firestein and Shepherd, 1992;Kurahashi et al, 1994;Mathis et al, 2016;Rospars et al, 2008Rospars et al, , 2000Singh et al, 2019) (also bioRxiv preprints; Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). However, the prevalence of these interactions, especially in living animals within the constraints of natural sniffing dynamics, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition or antagonism has been previously observed for single receptor neurons tested with monomolecular compounds 8,[18][19][20][21][22][23] . Moreover, multiple mathematical and biophysical models have been proposed to describe the consequences of mixing two odors that included suppression and/or inhibition 21,[35][36][37] . However, the low throughput of classical methods to assess cell-specific responses to multiple odors has made it very difficult to quantify the incidence of inhibition in practice and therefore tis relevance to perception.…”
Section: Discussionmentioning
confidence: 99%